Analisis Usability Portal Akademik Berbasis Web Menggunakan USE Questionnaire - Sipayung, Evasaria Magdalena; Susilo, Willy Stevanus (Yayasan Petra Harapan Bangsa, 2021)
The usability level of web-based academic portals used in distance learning during the Covid-19 pandemic needs to be measured. If there are some difficulties or problems in the portal, then can be repaired. The user interface improvement refers to usability as a quality measure used to assess the ease of use of the user interface. Usability is measured using the USE Questionnaire.. The USE Questionnaire is one of the questionnaires used to measure usability. The USE Questionnaire is consisted of 30 questions and is divided into four criteria: usefulness, ease of use, ease of learning, and satisfaction. Each of these criteria is broken down into a set of statements that are given to users. The statement is in the form of a questionnaire with a Likert scale. Based on the usability criteria used in the USE Questionnaire, the usability measurement of the academic portal is carried out. The measured academic portals consist of lecturer portals and academic portals. The results showed that academic portals were generally well-received by users. The academic portals are considered useful and helpful to work. Tingkat usability Portal Akademik berbasis web yang digunakan pada pembelajaran jarak jauh di masa pandemi Covid-19 perlu diukur. Jika ditemukan kesulitan atau masalah dalam penggunaan portal tersebut, maka dapat dilakukan perbaikan. Perbaikan user interface mengacu pada usability, yaitu ukuran kualitas yang digunakan untuk menilai kemudahan penggunaan user interface. Pengukuran usability dilakukan dengan menggunakan USE Questionnaire. USE Questionnaire merupakan salah satu kuesioner yang digunakan untuk mengukur usability. USE Questionnaire terdiri atas 30 pertanyaan dan dibagi ke dalam empat kriteria, yaitu usefullness, ease of use, ease of learning, dan satisfaction. Setiap kriteria tersebut diuraikan menjadi sekumpulan pernyataan yang diberikan kepada para pengguna. Pernyataan tersebut dalam bentuk kuesioner dengan skala Likert. Berdasarkan kriteria usability yang digunakan pada USE Questionnaire, maka dilakukan pengukuran usability Portal Akademik. Portal akademik yang diukur terdiri atas Portal Dosen dan Portal Akademik. Hasil penelitian menunjukkan Portal Akademik secara umum dapat diterima dengan baik oleh user. Portal akademik dianggap bermanfaat dan dapat membantu pekerjaan.